2019
DOI: 10.1096/fj.201901618rr
|View full text |Cite
|
Sign up to set email alerts
|

The RNA‐binding protein ILF3 binds to transposable element sequences in SINEUP lncRNAs

Abstract: Transposable elements (TEs) compose about half of the mammalian genome and, as embedded sequences, up to 40% of long noncoding RNA (lncRNA) transcripts. Embedded TEs may represent functional domains within lncRNAs, providing a structured RNA platform for protein interaction. Here we show the interactome profile of the mouse inverted short interspersed nuclear element (SINE) of subfamily B2 (invSINEB2) alone and embedded in antisense (AS) ubiquitin C-terminal hydrolase L1 (Uchl1), an lncRNA that is AS to Uchl1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…NONO is known as a core component of paraspeckles in nuclei along with the lncRNA NEAT1 , and these paraspeckles may relate to transcriptome functional regulation and retention in the nucleus ( 50–53 ). ILF3 (Interleukin enhancer-binding factor 3) is known as RNA binding protein to participate in regulation of RNA splicing, stabilization ( 54 , 55 ) and nuclear retention to bind with transposable element in SINEUPs ( 56 ). Here, although we observed that some SINEUP-GFP RNAs were retained in the nucleus and co-localized with RBPs ( Supplementary Figure S2A ), we could not characterize these nuclear granules containing SINEUP RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…NONO is known as a core component of paraspeckles in nuclei along with the lncRNA NEAT1 , and these paraspeckles may relate to transcriptome functional regulation and retention in the nucleus ( 50–53 ). ILF3 (Interleukin enhancer-binding factor 3) is known as RNA binding protein to participate in regulation of RNA splicing, stabilization ( 54 , 55 ) and nuclear retention to bind with transposable element in SINEUPs ( 56 ). Here, although we observed that some SINEUP-GFP RNAs were retained in the nucleus and co-localized with RBPs ( Supplementary Figure S2A ), we could not characterize these nuclear granules containing SINEUP RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our analysis by icSHAPE showed high-enrichment-score protected regions in the T domain, further validating the presence of a single-strand region in this domain in living cells, whereas low-enrichment-score regions in the T domain were preferentially double-stranded as a result of the constraints of the RNAfold software ( Supplementary Figure S5 , see ‘Materials and Methods’ section) ( 38 , 53 ). Thus, our NMR results provide new insights into the RNA regions of inverted SINE B2, and the T domain dynamics may be applicable to binding proteins for SINEUP activity in living cells ( 54 , 55 ). They therefore emphasize the importance of experiment-based structural examination.…”
Section: Discussionmentioning
confidence: 88%
“…A recently described class of lncRNAs, called SINEUPs, up-regulates translation through an embedded inverted SINE element that forms a short hairpin [ 201 , 202 ]. This hairpin has been shown to be essential for the up-regulation function of SINEUP lncRNAs and serves as a recognition motif for the RNA-binding protein ILF3 (IL enhancer-binding Factor 3) [ 203 ]. The first representative member of this family, which was described in mouse, is responsible for the translational regulation of the ubiquitin carboxy-terminal hydrolase L1 ( uchl1/PARK5 ), which is essential for brain function and particularly for neuron maintenance [ 201 , 204 , 205 ].…”
Section: Tes As a Source Of New Non-coding Rna Genesmentioning
confidence: 99%